Reducing prescribing error: competence, control, and culture. (26th November 2003) - Barber, N; Rawlins, M; Dean Franklin, B
Abstract : Medication errors are probably the most prevalent form of medical error, and prescribing errors are the most important source of medication errors. In this article we suggest interventions are needed at three levels to improve prescribing: (1) improve the training, and test the competence, of prescribers; (2) control the environment in which prescribers perform in order to standardise it, have greater controls on riskier drugs, and use technology to provide decision support; and (3) change organisational cultures, which do not support the belief that prescribing is a complex, technical, act, and that it is important to get it right. Solutions involve overt acknowledgement of this by senior clinicians and managers, and an open process of sharing and reviewing prescribing decisions.